Time-dependent dynamics of an intense laser-induced above-threshold Coulomb explosion - Esry, B. D.; Ben-Itzhak, I. (My University, 2010)
We use our recently proposed model to extract information about the nuclear dynamics from the Coulomb explosion data of Staudte et al. [Phys. Rev. Lett. 98, 073003 (2007)]. Those data, taken at multiple intensities near the ionization appearance intensity for both H2 and D2 in linearly and circularly polarized light, show remarkable structure and regularity not easily explained by conventional models. Because our model does fit the spectra well, we can infer the qualitative time-dependent evolution of the system. In addition, it suggests a possible experimental signature of rescattering leading to above-threshold Coulomb explosion.